Time Required to Create a Referral in Various Store-and-Forward Telemedicine Networks - Wootton, Richard; O'Kane, Barry (Frontiers in Public Health, 2019)
Store and forward telemedicine is used routinely in health care, but there is little published information about how such telemedicine systems are used. For example, an important aspect of the system's usability is the length of time it takes to submit a referral. Referral-submission times were measured in networks based on the Collegium Telemedicus system. In a 25-week period in 2018/2019, eight Collegium networks received a total of 1,649 clinical or educational cases submitted via the web interface. The time to prepare a referral was measured in 669 of these cases, in two different ways. An indirect measurement of the referral-preparation time was calculated as the interval between the user logging in, and the referral being submitted. A direct measurement of the referral-preparation time was calculated as the interval between the user opening the referral page and the referral being submitted to the server. The difference between the two measurements represents time spent by the user on other activities after logging in, before beginning the referral. The median referral-preparation time, measured directly, was 888 s (IQR 512-1765). The median of the differences between the two preparation times was 27s (IQR 8-146). The referral-preparation times in the eight networks were broadly similar, despite the differences in the nature of their operation (clinical or educational), and the types of case handled (single specialty or multi-specialty). Quantitative information about aspects of the user interface, such as the referral-preparation time, is important not only in the initial system design, but also in its subsequent development.